2023
DOI: 10.3390/jcm12227111
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation for Tachyarrhythmias in Left Ventricular Assist Device Recipients: Clinical Significance and Technical Tips

Naoya Kataoka,
Teruhiko Imamura

Abstract: The demand for durable left ventricular assist devices (LVADs) has been increasing worldwide in tandem with the rising population of advanced heart failure patients. Especially in cases of destination therapy, instead of bridges to transplantation, LVADs require a lifelong commitment. With the increase in follow-up periods after implantation and given the lack of donor hearts, the need for managing concomitant tachyarrhythmias has arisen. Atrial and ventricular arrhythmias are documented in approximately 20% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Given the altered anatomy and continuous blood flow support provided by LVADs, safety is paramount during ablation procedures. Several studies have demonstrated the utility of ICE in visualizing the LVAD inflow cannula, outflow graft, and adjacent structures, enhancing the safety and efficacy of catheter ablation [ 61 , 62 , 63 ]. Intracardiac echo aids in the visualization of potential complications, such as catheter entrapment or interference with LVAD components, minimizing the risk of adverse events [ 61 ].…”
Section: Catheter Ablation In Patients With Lvads and Ventricular Arr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the altered anatomy and continuous blood flow support provided by LVADs, safety is paramount during ablation procedures. Several studies have demonstrated the utility of ICE in visualizing the LVAD inflow cannula, outflow graft, and adjacent structures, enhancing the safety and efficacy of catheter ablation [ 61 , 62 , 63 ]. Intracardiac echo aids in the visualization of potential complications, such as catheter entrapment or interference with LVAD components, minimizing the risk of adverse events [ 61 ].…”
Section: Catheter Ablation In Patients With Lvads and Ventricular Arr...mentioning
confidence: 99%
“…Studies evaluating the impact of intracardiac echo on clinical outcomes in VT ablation in LVAD patients are limited but encouraging. Improved procedural success rates, reduced recurrence of VT, and enhanced patient safety have been reported in cohorts where ICE was integrated into the ablation strategy [ 61 , 62 , 63 ]. While further research is needed to establish standardized protocols and assess long-term efficacy, current evidence supports the routine use of intracardiac echo in VT ablation for LVAD patients.…”
Section: Catheter Ablation In Patients With Lvads and Ventricular Arr...mentioning
confidence: 99%